VALUASI EKONOMI DAMPAK PENCEMARAN DI SUB DAS CISANGKUY - Nandang Najmulmunir (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam 45, 2004)
The water pollution from any sources is the externality, for example the water river basin pollution caused by manufacture industry, such textile industry is the social cost and it has to be internalized in to economic cost structure. But the pollution has no price and market. The economic valuation is the one method for emerging the value of that pollution.